The Effect of Scaffolded Project Based Learning on Students’ Critical Thinking Skills to Support SDG 4 - Martini Martini; Erman Erman; I Gusti Made Sanjaya (Journal of Current Studies in SDGs, 2026)
Objective: To examine the effect of scaffolded Project-Based Learning on junior high school students’ critical thinking skills in science learning on the topic of food additives.  Method: Employing a quantitative approach using a quasi-experimental pretest-posttest design involving three intact junior high school classes (Classes 8E, 8F, and 8H). Students participated in scaffolded Project-Based Learning activities on the topic of food additives.  Results: The findings revealed that scaffolded Project-Based Learning effectively improved students’ critical thinking skills across the three participating classes. The mean N-Gain scores reached 0.70 in Class 8E, 0.94 in Class 8F, and 0.91 in Class 8H, all of which were categorized as high. The greatest improvements were consistently observed in the interpretation, inference, and self-regulation indicators, while the explanation and evaluation indicators demonstrated comparatively lower gains in some classes. These findings indicate that integrating structured scaffolding into Project-Based Learning effectively promotes higher-order thinking by supporting students in interpreting information, analyzing contextual problems, drawing evidence-based conclusions, and regulating their own learning processes. Novelty: Extends previous research by integrating structured scaffolding into Project-Based Learning to strengthen junior high school students’ critical thinking skills in science learning on the topic of food additives. Furthermore, the study contributes to the implementation of Sustainable Development Goal (SDG) 4 by providing empirical evidence that scaffolded Project-Based Learning promotes meaningful, student-centered, and competency-based science education that develops essential twenty-first-century skills.